Impact of Colonial Governance on Modern Civic Administration in Bangalore: Legacy, Renewal, and Reconfiguration - Manjula R. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
In this paper, the continuity between the colonial process of civic governance and the development of the modern model of municipal administration in Bangalore is studied, considering the recent structural changes in the city. The British rule piloted in municipal institutions, infrastructure, and administrative structures that formed a base on which independent India established its civic order. These colonial precedents, too, however, were marked by strict hierarchies and spatial inequalities. The state government superseded the Bruhat Bengaluru Mahanagara Palike (BBMP) with the Greater Bengaluru Authority (GBA). It split the city into five corporations in 2025 to decentralize and modernize administration. Examining the innovations of colonial times, post-independence legacies and the rationale of contemporary rearrangements, the paper maintains that Bangalore is reworking its colonial legacies - retaining its administrative assets and coping with new urban demands. The new composition reflects the burden of the past and the possibility of institutional regeneration.